Analisis Perbedaan Tanaman Kayu Apu (Pistia stratiotes) sebagai Fitoremediasi Merkuri (Hg) pada Air - Maulida Khasanah; Anita Dewi Moelyaningrum; Rahayu Sri Pujiati (Sanitasi: Jurnal Kesehatan Lingkungan, 2018)
Amalgamation in the activities of gold processing produces liquid waste containing heavy metals mercury (Hg). Pistia stratiotes is a floating plant that has high adaptability to climate, rapidgrowth rate, and huge nutrients and water absorption.So that, it is possible to be used as phytoremediation plant for absorbing Hg in water. The purpose of this true experiment research wasto analyze the Hg concentration differences between waste water with and without Pistia stratiotes of 300 gr/ 6 l, 400 gr/ 6 l and 500 gr/ 6 weight in 10 days contact time. The data were analyzed by using One Way Anova test at ? = 0,05. The results showed significant differences ofHg levels between control and treatment groups (p<0,05), and 500 gr/6 l Pistia stratiotes weightgave the highest reduction of Hg level in liquid waste, i.e. 77,6 %. It can be concluded that Pistia stratiotes can be used as phytoremediation plant for Hg metal. However, it is necessary todo further research by adding contact times as variable, so that the absorption rate at each timecan be determined.